PERBANDINGAN PERKEMBANGAN ZAKAT-WAKAF DI BRUNAI DAN DI INDONESIA - Nova Andriyani (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
The aim of this research is to discuss the development of zizwaf in Brunei and Indonesia and also the institutions that handle zizwaf in these two countries. Apart from that, it also discusses differences and similarities in management, institutions and distribution. This type of research uses qualitative research methods to analyze zizwaf regulations between the two countries. Data collection will be carried out through a literature review to gain an in-depth understanding of the regulations and the differences and similarities between zizwaf in the two countries. Primary data will be obtained from literature and also laws and zizwaf books. Secondary data will be obtained from legal documents, regulations and laws. The results of this research are that Zizwaf in Indonesia is managed by BWI, while in Brunei Darussalam it is managed and is the responsibility of the Brunei Islamic Religious Council (MUIB).